Pelatihan Pengelolaan Keuangan Pribadi Bagi Mahasiswa/I Di Asrama Kabupaten Fak-Fak - Pascalina Van Sweet Sesa; Hesty Theresia Salle; Klara Wonar (UNIVERSITAS CENDERAWASIH, 2022)
One of the intelligences that modern humans must possess is financial intelligence, which is intelligence in managing personal financial assets. The results of the 2019 national survey showed that the financial literacy rate of the population aged 15-17 years was 16% which indicates a low level and is more financially vulnerable in the sense of being able to spend money on pleasure than to save or invest to add assets. Thus, one way to respond to finances is how individuals can control their personal finances. Personal financial management training for students is carried out by the method of lectures, discussions, and exercises to identify needs and calculate the monthly expenses of students. To ensure that participants can understand the learning outcomes, at the end of this learning a posttest is carried out in the form of providing a simple survey to test the level of knowledge, attitudes, and behaviors of managing personal finances of students. The conclusion that can be made in the Student Personal Financial Management Training is to ensure that this training can provide an increase in understanding or level of financial literacy to the younger generation in planning for the future and their finances properly.